2019
DOI: 10.1002/rmb2.12306
|View full text |Cite
|
Sign up to set email alerts
|

Effect of moderately increased thyroid‐stimulating hormone levels and presence of thyroid antibodies on pregnancy among infertile women

Abstract: PurposeTo study the effects of mildly elevated thyroid‐stimulating hormone (TSH) levels and thyroid antibodies on pregnancy rates among infertile women and their potential contribution to prolonged infertility treatment.MethodsThis case‐control study included 1479 women who underwent infertility treatment between March 2015 and August 2017. Cumulative pregnancy and miscarriage rates after assisted reproductive technology (ART) or non‐ART treatments were compared between women with TSH <2.5 mIU/L and those w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 28 publications
2
2
0
Order By: Relevance
“…Chai et al also reported that the clinical pregnancy rate and miscarriage rate were not impaired when the TSH level was high-normal [ 8 ]. In agreement with our results, So et al and Unuane et al both claimed that cumulative pregnancy rates were similar between women with low TSH levels and those with high-normal TSH levels [ 4 , 7 ].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Chai et al also reported that the clinical pregnancy rate and miscarriage rate were not impaired when the TSH level was high-normal [ 8 ]. In agreement with our results, So et al and Unuane et al both claimed that cumulative pregnancy rates were similar between women with low TSH levels and those with high-normal TSH levels [ 4 , 7 ].…”
Section: Discussionsupporting
confidence: 93%
“…However, there is insufficient evidence indicating an association between mildly elevated preconception TSH (2.5-4.0 mIU/L) and the abovementioned reproductive outcomes [3]. In recent years, studies investigating the impact of mildly elevated TSH levels on infertile women have emerged [4][5][6][7][8][9][10][11][12][13][14]. However, when infertile women underwent in vitro fertilization or intracytoplasmic sperm injection (IVF/ICSI) treatment, the conclusion of the impact of mildly elevated TSH levels on miscarriage and obstetric outcomes in women of reproductive age was still inconsistent in different studies, in which various confounders (such as the transfer of cleavage embryo or blastocysts, the number and quality of the transferred embryo, and the age of included women) influenced the reproductive outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…Chai et al also reported that the clinical pregnancy rate and miscarriage rate were not impaired when the TSH level was high-normal [ 8 ]. In agreement with our results, Unuane et al and So et al both claimed that cumulative pregnancy rates were similar between women with low-TSH levels and those with high-normal TSH levels [ 5 , 14 ].…”
Section: Discussionsupporting
confidence: 93%
“…Similar results were also observed in women undergoing the first single fresh D5 blastocyst transfer. However, different opinions were held by other instigators as various confounders (such as the transfer of cleavage embryo or blastocysts, the number and quality of the transferred embryo, and the age and ethnicity of included women) influenced the reproductive outcomes [ 5 14 ]. For that reason, the aim of this study was to further evaluate the impact of preconception TSH levels between 2.5 and 4.2 mIU/L (which was used as the upper limit of the reference range in our laboratory) on reproductive outcomes in women undergoing their first fresh D3 embryo transfer.…”
Section: Introductionmentioning
confidence: 99%